La revista de psicología contemporánea : análisis y perspectivas - Oblitas Guadalupe, Luis Armando (1998)
The Journal of Contemporary Psychology (Revista de Psicología Contemporánea RPC) a periodic publication of the Editorial el Manual Moderno (MM) is celebrating its 5th birthday. In the present study a description of some significant experiences along the first five years of RPC are described, focused on the communication between the author and MM, among the collaborators, subscriptions, promotions and forum participation, among others. An analyses of the published articles is also presented as well as the tendencies for the future. The present article will be of interest for psychologists that develop editorial activities or that are going to begin the edition of a journal of psychology.